Cations and dications of heavier group 14 elements in low oxidation states - Swamy, V. S. V. S. N.; Pal, Shiv; Khan, Shabana; Sen, Sakya S. (Dalton Transactions, 2015)
Cations and dications of heavier group 14 elements in their low oxidation state have received widespread attention in recent years. The journey started with the isolation of a series of cations of the composition [(C5Me5)E:](+) [E = Si-Pb], followed by the more recent isolation of a Ge(II) dication encapsulated within a cryptand, a carbodiphosphorane stabilized [GeCl](+) monocation with a two coordinate Ge atom, Si(II) cations and dications stabilized by N-heterocyclic carbenes (NHCs), which highlights the ongoing growth and interest in the chemistry of tetrel(II) cations. This is presumably because the central atom (E) in these compounds contains two or three unoccupied valence orbitals as well as holds a lone pair of electrons. Such an electronic description represents ambiphilicity, which is of great interest for catalysis. The successful synthesis of divalent group 14 cations requires new synthetic strategies based on the sterically demanding neutral or monoanionic ligands, utilization of counter anions, and solvents with low nucleophilicity in order to minimize the degree of interactions with the cations. An alternative approach for the realization of divalent cations of group 14 elements is their coordination to the transition metals. This synthetic approach was successfully applied for the isolation of a range of transition metal coordinated divalent cations of group 14 elements. Apart from arousing academic interest some of these cations have found application as activators in the Ziegler-Natta polymerization of alkenes.

Compounds with low-valent p-block elements for small molecule activation and catalysis - Yadav, Sandeep; Saha, Sumana; Sen, Sakya S. (Chemcatchem, 2016)
The past decade has witnessed staggering progress in the chemistry of compounds with low-valent main-group elements. Although these discoveries are mostly fundamental by nature, these compounds show promising reactivity towards small molecule activation. The reactivity of these compounds stems from the modest HOMO-LUMO energy gap; a characteristic known for the transition metals. The journey began in 2005 with the facile activation of dihydrogen by an alkyne analog of germanium [ArGeGeAr; Ar=2,6-Trip(2)-C6H3 (Trip=2,4,6-iPr(3)-C6H2)]. Subsequently, tremendous progress has been achieved in understanding and elucidating the potential of these compounds to activate small molecules as well as to use them in a variety of stoichiometric and catalytic transformations. In this review, we focus on developments in the activation of H-2, NH3, CO, and CO2 by compounds with multiply bound or open shell main-group elements. Emphasis will be given to their catalytic activity.
Keywords: activation; carbenes; main-group elements; silylenes; small molecules

C(sp(3))-F, C(sp(2))-F and C(sp(3))-H bond activation at silicon(II) centers - Swamy, V. S. V. S. N.; Parvin, Nasrina; Raj, K. Vipin; Sen, Sakya S. (Chemical Communication, 2017)
Silylene [PhC(NtBu)(2)SiN(SiMe3)(2)] (1) cleaves the C(sp(3))-H and C-F bonds of acetophenone and 1,1,1-trifluoroacetophenone, respectively, under mild conditions. The reaction is initiated via a nucleophilic attack from the oxygen to the silicon atom followed by C-F/H bond cleavage. The scope of C-F bond activation has further been extended with C6F6 and C6F5CF3.
Keywords: Boron triple bond; C-F Bond; Fluorinated Building-Block; H Activation; Ketones; N-heterocyclic carbenes; Oxodative Addition; Perfluorinated Arenes; Selective Activation; Transition-Metal Centers

Cyclometallation of a germylene ligand by concerted metalation-deprotonation of a methyl group - Bakthavachalam, K.; Dutta, Sayan; Arivazhagan, C.; Raghavendra, Beesam; Haridas, Anagha; Sen, Sakya S.; Koley, Debasis; Ghosh, Sundargopal (Dalton Transactions, 2018)
The reaction of [CH{(CMe)(2,6-iPr(2)C(6)H(3)N)}(2)]GeCl with LiN(SiMe3)(2) was previously reported, which led to the formation of a hetero-fulvene type germylene, [CH{(CMe)(C?CH2)(2,6-iPr(2)C(6)H(3)N)}(2)]Ge through the deprotonation of the C-H bond from the methyl substituents. In this paper, we attempted the analogous reaction with (Dipp)NCMeCHCOMeGeCl using LiN(SiMe3)(2) which gave rise to a metathesis product, (Dipp)NCMeCHCOMeGeN(SiMe3)(2) (2). However, the reactions of 2 with [M2Cl2(-Cl)(2)((5)-Cp*)(2)] (M = Rh and Ir) resulted in cyclometallated Rh and Ir complexes through the activation of the C-H bond from the germylene ligand. The complexes were characterized by single crystal X-ray analysis, which authenticated the presence of Ge-Rh and Ge-Ir bonds. DFT studies have been performed to understand the mechanism.

Cyanosilylation by compounds with main-group elements: an odyssey - Pahar, Sanjukta; Kundu, Gargi; Sen, Sakya S. (ACS Omega, 2020)
The past few decades have seen remarkable headways in the structural and reaction chemistry of compounds with heavier main-group elements. In recent years, there is an ongoing effort to derive catalytic chemistry involving main-group compounds, driven by their lower costs and higher terrestrial abundances. Here, a survey on the state-of-the-art in the development of cyanosilylation methodology by compounds with heavier main-group elements has been given. Once dominated by transition metals, the field has matured to embrace the majority of the main-group elements including aluminum, silicon, and calcium. Of particular focus will be how the mechanism of cyanosilylation involving compounds with main-group elements differs from those of transition metals.

On the competition between six-membered and five-membered NHC towards alane centered ring expansion - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Ravindranathan, Sapna; Gonnade, Rajesh G.; Sen, Sakya S. (Chemical Communications, 2023)
The combination of 6-SIDipp center dot AlH3 (1) and 5-IDipp resulted in the ring expansion of 6-NHC, while the five-membered NHC remained unchanged, which was subsequently explained by DFT studies. Besides, the substitution chemistry of 1 was also studied with TMSOTf and I-2, which gave rise to the substitution of a hydride by triflate or iodide ligands.

Controlled reduction of isocyanates to formamides using monomeric magnesium - Kumar, Rohit; Sharma, Vishal; Banerjee, Subhrashis; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2023)
This work describes a transition metal-free methodology involving an efficient and controlled reduction of isocyanates to only formamide derivatives using pinacolborane (HBpin) as the hydrogenating agent and a bis(phosphino)carbazole ligand stabilized magnesium methyl complex (1) as the catalyst. A large number of substrates undergo selective hydroboration and give exclusively N-boryl formamides.

C=C insertion over N=C=O of allyl isocyanate into the Ge-Si bond of a germylene - Ajithkumar, V. S.; Khilari, Nripen; Ghanwat, Pratiksha B.; Koley, Debasis; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2025)
Two isocyanates are reacted with the germylene, PhC(NtBu)(2)Ge-Si(SiMe3)(3) (1). Phenyl isocyanate undergoes catalytic cyclotrimerization with 1 leading to 1,3,5-triphenyl isocyanurate (2), while allyl isocyanate undergoes both cyclotrimerization and the C=C bond insertion between the Ge-Si bond. The constitution of 3 is determined by single-crystal X-ray studies. The contrasting reactivity pattern is explained by comprehensive density functional theory studies.
Keywords: Cyclotrimerization; Density functional theory; Germylene; Insertion; isocyanates